Ska Grisness Culture Music in the Music Industry and Its Implications in Arts Education - Asmarani, Kidung Sukma; Wadiyo, Wadiyo; Sunarto, Sunarto (Catharsis, 2020)
The aims of this study is to explain and reveal how Grisness Culture musical works can compete in the music industry and its implications in arts education. This study uses an interdisciplinary approach with qualitative analytical methods. The research design used a case study and the focus of the research was on the ska music of the Grisness Culture group. The data collection techniques used were observation, interview, and documentation study. The data validation used triangulation techniques with data analysis techniques by using interactive models. The results of this study are Grisness Culture was able to compete in the music industry with the capital they have, namely economic, cultural, social, and symbolic capital as well as marketing activities, namely the production of works, promotion, and distribution. Second, the activities carried out during the work to marketing process lead to artistic experiences through art activities, namely appreciation, creation and expression that can create arts education in a broader context in the music industry and have implications in the form of character values.